The nutritional impacts of soil-transmitted helminths infections among Orang Asli schoolchildren in rural Malaysia - Ahmed, A.; Al-Mekhlafi, H.M.; Al-Adhroey, A.H.; Ithoi, I.; Abdulsalam, A.M.; Surin, J. (BMC, 2012)
Background: Soil-transmitted helminths (STH) infections, anaemia and malnutrition are major public health problems in school-age children in developing countries. This study was conducted on 289 Orang Asli (aboriginal) schoolchildren in order to assess the current prevalence and predictors of anaemia and malnutrition, as well as the nutritional impacts of STH infections among these children. Methods: A cross-sectional study was combined with a longitudinal follow-up three months after treatment with anthelminthic drugs. Blood samples were collected from the children to measure haemoglobin (Hb) level. Anthropometric and socioeconomic data were also collected and the children were screened for STH. Results: The baseline findings revealed that the prevalence of anaemia, significant stunting, underweight and wasting among the children were 41.0, 28.0, 29.2 and 12.5, respectively. Overall, the prevalence of trichuriasis, ascariasis and hookworm infections were 84.6, 47.6 and 3.9, respectively. Haemoglobin level was significantly lower among the moderate-to-heavy infected children compared to the negative-to-light infected children. Age < 10years and moderate-to-heavy ascariasis were the predictors of anaemia. Stunting was associated with gender, age, moderate-to-heavy ascariasis and trichuriasis. Three months post-treatment assessment showed that the moderate-to-heavy infected children gained significant increment in their mean Hb level compared to the negative-to-light infected children (0.44 g/dL compared to 0.08 g/dL). However, no difference was found in the mean increments in growth indices between the groups. Conclusion: STH infections, anaemia and malnutrition are still prevalent and a matter of public health concern in Orang Asli communities in Malaysia. Sustainable deworming programme at school and community levels among these populations will help to improve their health and nutritional status.